Ketamine can reduce harmful drinking by pharmacologically rewriting drinking memories - Ravi K. Das; Grace Gale; Katie Walsh; Vanessa E. Hennessy; Georges Iskandar; Luke A. Mordecai; Brigitta Brandner; Merel Kindt; H. Valerie Curran; Sunjeev K. Kamboj (Nature Communications, 2019)
Memories linking environmental cues to alcohol reward are involved in the development and maintenance of heavy drinking. Here, the authors show that a single dose of ketamine, given after retrieval of alcohol-reward memories, disrupts the reconsolidation of these memories and reduces drinking in humans.